Liquid crystal polyester composition and preparation method and application thereof

Through the synergistic effect of the polyaryl in the liquid crystal polyester composition and the lipo exchange of liquid crystal polyester and linear low-density polyethylene, combined with the distribution of fibrous and sheet-like fillers, the bubble of liquid crystal polyester materials at high temperatures is solved. The problem of insufficient wear resistance achieves better bonding and lubricity of the leather core layer and improves the overall performance of the material.

CN116640420BActive Publication Date: 2024-12-31ZHUHAI WANTONG SPECIAL ENG PLASTICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310479474.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2024-12-31
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

After the high-temperature process, liquid crystal polyester materials have different thermal expansion characteristics of the leather and core layers, which lead to interlaced internal stress, which in turn causes bubble problems, especially in thin-walled molds, which affects assembly and contact performance.

Method used

Using a liquid crystal polyester composition, including liquid crystal polyester, filler, coupling agent, linear low density polyethylene (LLDPE) and polyaryl esters, the surface crystallinity is reduced through the exchange of polyaryl esters with liquid crystal polyesters, linear crystalline properties, linear The type low-density polyethylene improves lubricity and enhances the bonding and wear resistance of the core layer through the distribution of fibrous and sheet-like fillers.

Benefits of technology

It significantly improves the high temperature and foam resistance and wear resistance of liquid crystal polyester. By uniformly distributing fillers and enhancing interface bonding, the difference in the leather core layer is reduced and the overall performance of the material is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a liquid crystal polyester composition, which comprises the following components by weight: 50-100 parts of liquid crystal polyester; 12-40 parts of filler; 0.1-3 parts of coupling agent; 0.2-0.6 parts of linear low-density polyethylene; 1-4 parts of polyarylate; wherein the filler is selected from fibrous filler and flaky filler, and the weight ratio of the fibrous filler and the flaky filler is (0.6-50): 1; the liquid crystal polyester is composed of at least two of terephthalic acid, biphenyl, 6-hydroxy-2-naphthoic acid, and p-hydroxybenzoic acid and acetaminophen as repeating units. The liquid crystal polyester composition of the invention can achieve a higher degree of enrichment of wear-resistant filler in the material resin skin layer through the compounding of fibrous filler and flaky filler and the compounding of linear low-density polyethylene and polyarylate, thereby significantly improving the wear resistance, and has excellent high temperature resistance and anti-foaming performance due to the good skin / core layer bonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a liquid crystal polyester composition and a preparation method and application thereof. Background Art

[0002] The molecular chain of LCP material is a highly ordered rod-like structure. There are a large number of benzene rings, biphenyl and other structures in the monomer. The molecular chain shows liquid crystal properties in the molten state. During injection molding, the high-speed flow of the melt and the extremely fast cooling speed in the thin-walled mold easily form a skin layer on the surface of the molded object. The cooling rate of the interior and the skin layer is different, forming a special skin-core structure.

[0003] LCP products are mostly used in SMT processes. After high-temperature processes, the different thermal expansion characteristics of the skin and core layers will cause staggered internal stress between the skin and core layers, leading to peeling between the two phases, which in turn causes blistering. Especially in thin-walled molds where thickness conversion and flow direction turning points occur, the rapid surge of the melt can easily wrap up the gas in the mold cavity, the skin cools quickly, and the gas is compressed in the core layer and between the skin and core layers. After heat expansion, it will accelerate the separation of the skin and core, causing surface blistering. The blistering of thin-walled parts can cause problems such as poor assembly and contact, which is more obvious in products assembled with metal parts. For example, in rotary encoders, LCP products need to contact and rub metal springs to obtain signal transmission and recognition.

[0004] Generally, some wear-resistant fillers and surface modifiers are added to improve wear resistance, but this can easily lead to poor skin / core bonding.

[0005] However, the prior art requires that the liquid crystal polyester composition has both high temperature resistance, anti-foaming and wear resistance. In order to obtain a high temperature resistance, anti-foaming and wear-resistant liquid crystal polymer, it is necessary to control the distribution of the wear-resistant material between the skin and the core and improve the bonding strength between the skin and the core layers. Summary of the invention

[0006] The object of the present invention is to provide a high temperature resistant, anti-foaming and wear resistant liquid crystal polyester, and a preparation method and application thereof.

[0007] The present invention is achieved through the following technical solutions:

[0008] A liquid crystal polyester composition, comprising the following components in parts by weight:

[0009] Liquid crystal polyester 50-100 parts;

[0010] 12-40 parts of filler;

[0011] Coupling agent 0.1-3 parts;

[0012] LLDPE 0.2-0.6 parts;

[0013] 1-4 parts of polyarylate;

[0014] Wherein, the filler is selected from fibrous filler and flaky filler, and the weight ratio of fibrous filler to flaky filler is (0.6-50):1; the liquid crystal polyester is composed of at least two of terephthalic acid, biphenyl, 6-hydroxy-2-naphthoic acid, and p-hydroxybenzoic acid and acetaminophen as repeating units.

[0015] The retention length is the fiber length of the fibrous filler retained in the resin matrix.

[0016] Preferably, the polyarylate is composed of diphenol units and dicarboxylic acid units: the diphenol units are derived from bisphenol A, and based on the molar percentage of the dicarboxylic acid units, terephthalic acid accounts for 40-60 mol% of the dicarboxylic acid units, and isophthalic acid accounts for 40-60 mol% of the dicarboxylic acid units.

[0017] The polyarylate for realizing the technical purpose of the present invention can be a commercially available product or a homemade raw material. The following method can be used for homemade production: the purified bisphenol A diacetate, terephthalic acid, and isophthalic acid are fully dried at 90°C and then put into a reactor in a certain proportion, and vacuum and nitrogen are filled to ensure that the air in the reactor is discharged. Slowly heat to 120°C and keep warm for 30 minutes to discharge moisture. Slowly heat to 230-250°C under nitrogen protection, keep warm until acetic acid distills out, maintain vacuum, react until acetic acid no longer distills out, then quickly heat to 330-340°C, vacuum and stir, and stop stirring after a period of reaction. During the reaction, the pressure in the reactor needs to be maintained at 0.5-0.8 atmospheres.

[0018] Preferably, the weight ratio of the fibrous filler to the flaky filler is (2-7):1.

[0019] Preferably, the weight portion of LLDPE is 0.3-0.5 parts, and the weight portion of polyarylate is 2-3 parts.

[0020] LLDPE is linear low-density polyethylene with a melt index range of 3-80g / 10min, 2.16kg, 190℃.

[0021] The present invention has no particular restrictions on the polyarylate, and also has no particular restrictions on the molecular weight of the polyarylate, and the purpose of the present invention can be achieved when the solution viscosity is 0.3-1dL / g. The solution viscosity test method uses tetrachloroethane as a solvent, refers to GB / T 1632.1-2008 standard, and is measured using a capillary viscometer.

[0022] The repeating unit combination of LCP resin can be:

[0023] A: terephthalic acid / biphenol / acetaminophen, wherein the molar ratio of terephthalic acid / acetaminophen is (20-2):1.

[0024] B: terephthalic acid / biphenol / 6-hydroxy-2-naphthoic acid / acetaminophen, wherein the molar ratio of terephthalic acid / acetaminophen is (20-2):1.

[0025] C: terephthalic acid / biphenol / parahydroxybenzoic acid / acetaminophen, wherein the molar ratio of terephthalic acid / acetaminophen is (20-2):1.

[0026] D: terephthalic acid / biphenol / 6-hydroxy-2-naphthoic acid / parahydroxybenzoic acid / acetaminophen, wherein the molar ratio of terephthalic acid / acetaminophen is (20-2):1.

[0027] The above LCP resin has better dispersibility with fillers during the melt shearing process.

[0028] LCP resin can be a commercial product or can be obtained by self-production. The self-production method is:

[0029] Under inert gas pressure conditions, the reaction monomer is subjected to an acylation reaction under the action of an acylating agent, the pressure is maintained at 0.1 MPa to 0.2 MPa, the reaction temperature is 100°C to 180°C, and the reaction time is 30 minutes to 10 hours; after the acylation reaction is completed, the pressure in the reactor is reduced to normal pressure and the reaction mixture is heated at a rate of 0.1°C / min to 150°C / min. The temperature is raised to 200°C~400°C at a rate of 1.5°C, acetic acid and unreacted acetic anhydride are discharged from the distillation column, and when the amount of acetic acid received reaches more than 90% of the theoretical value, the pressure in the reactor is reduced to 1~10kPa, and the reduced pressure condition is maintained and the temperature of the reaction system is raised to the maximum reaction temperature of 320~360°C, and a prepolymer is obtained by melt polycondensation; the prepolymer is cooled, solidified and granulated, and solid-phase polymerization is carried out in a solid-phase polymerization container to obtain wholly aromatic liquid crystal polyester particles, the vacuum degree is 0.1Pa~50kPa, the solid-phase polymerization temperature is 160~340°C, and the reaction time is 0.5 hour~40 hours.

[0030] The acylating agent may be acetic anhydride, propionic anhydride, butyric anhydride or the like.

[0031] The LCP resin of the present invention is 20°C above the melting point and 1000 -s The melt viscosity under shear rate conditions is 10-50Pa·s. The test method for the melt viscosity of LCP resin is: based on the determination method of ISO 11443, at 20°C above the melting point, 1000 -s Under the shear rate conditions, the equipment used was a Goettfert high pressure capillary rheometer, RG20, with a 1 mm test die.

[0032] The fibrous filler is selected from at least one of glass fiber and carbon fiber. Preferably, the retention length range of the fibrous filler is 80-200 microns, and more preferably, the retention length range of the fibrous filler is 95-120 microns.

[0033] The flaky filler is selected from at least one of talc, flake graphite and mica. Preferably, the average particle size of the flaky filler is in the range of 5-30 microns, and more preferably, the average particle size of the flaky filler is in the range of 10-20 microns.

[0034] The coupling agent is selected from at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent, preferably a silane coupling agent.

[0035] You can choose whether to add 0-1 part of antioxidant according to actual needs.

[0036] The preparation method of the liquid crystal polyester composition of the present invention comprises the following steps: uniformly mixing the components, and then extruding and granulating through a twin-screw extruder, with the screw speed ranging from 400 to 600 RPM and the temperature ranging from 330 to 360° C. to obtain the liquid crystal polyester composition.

[0037] The liquid crystal polyester composition of the present invention is used for preparing thin-walled housings of electrical appliances.

[0038] The present invention has the following beneficial effects:

[0039] 1. The surface crystallinity of the composition is reduced by lipid exchange between polyarylate and liquid crystal polyester, and the linear low-density polyethylene improves the surface lubricity. The two work together to achieve uniform distribution of fillers in the resin cortex and core layer, improve the lubricity of the cortex, and are not easy to fall off, thereby significantly improving the wear resistance.

[0040] 2. Improve the bonding strength between the core layer and the skin layer, that is, by weakening the difference between the skin layer and the core layer and blurring the interface layer. On the one hand, the difference at the interface between the two phases is blurred through the synergistic effect of polyarylate / linear low-density polyethylene, and on the other hand, the bonding strength at the interface is increased through coupling agents.

[0041] 3. By examining the average particle size and retention length of fibrous fillers and flaky fillers, the wear resistance and foaming resistance can be further improved. Implementation

[0042] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0043] The sources of experimental raw materials used in the present invention are as follows:

[0044] LCP resin A: The repeating units are terephthalic acid / biphenol / acetaminophen, the molar ratio is 5:4.5:0.5, the melt viscosity is 27.2 Pa·s, and it is prepared by referring to the method described in the summary of the invention.

[0045] LCP resin B: The repeating units are terephthalic acid / biphenol / p-hydroxybenzoic acid / acetaminophen, the molar ratio is 8:5:3:3, the melt viscosity is 31 Pa·s, and it is prepared by referring to the method described in the summary of the invention.

[0046] LCP resin C: The repeating units are terephthalic acid / biphenol / 6-hydroxy-2-naphthoic acid / acetaminophen, the molar ratio is 4:3.2:1.5:0.8, the melt viscosity is 25.4 Pa·s, and it is prepared by referring to the method described in the invention content.

[0047] LCP resin D: The repeating units are terephthalic acid / biphenol / 6-hydroxy-2-naphthoic acid / p-hydroxybenzoic acid / acetaminophen, the molar ratio is 4:5:1:2:1, the melt viscosity is 29.5 Pa·s, and it is prepared by referring to the method described in the invention content.

[0048] LCP resin E: the repeating units are terephthalic acid / acetaminophen, the molar ratio is 1:1, the melt viscosity is 30.1 Pa·s, and it is prepared according to the method described in the summary of the invention.

[0049] LCP resin F: The repeating units are terephthalic acid / biphenol / 2-acetaminophenol, the molar ratio is 5:4.5:0.5, the melt viscosity is 28.9 Pa·s, and it is prepared by referring to the method described in the summary of the invention.

[0050] LCP resin G: The repeating units are terephthalic acid / biphenol, the molar ratio is 1:1, and the melt viscosity is 29.8 Pa·s. It is prepared by referring to the method described in the summary of the invention.

[0051] LCP resin H: repeating units are terephthalic acid / biphenol / 6-hydroxy-2-naphthoic acid / p-hydroxybenzoic acid, with a molar ratio of 2:2:1:1, and a melt viscosity of 30.2 Pa·s. It is prepared in-house according to the method described in the Summary of the Invention. LLDPE: ExxonMobil, ECD709, melt index 5 g / 10 min, 2.16 kg, 190°C;

[0052] Low-density polyethylene: Sinopec, PE M1870T 68g / 10min, 2.16kg, 190℃;

[0053] Polyarylate A: bisphenol A, terephthalic acid accounts for 40 mol% of the dicarboxylic acid unit, and isophthalic acid accounts for 60 mol% of the dicarboxylic acid unit, and is prepared by referring to the method described in the summary of the invention.

[0054] Polyarylate B: bisphenol A, terephthalic acid accounts for 60 mol% of the dicarboxylic acid unit, and isophthalic acid accounts for 40 mol% of the dicarboxylic acid unit, and is prepared by referring to the method described in the summary of the invention.

[0055] Polyarylate C: bisphenol A, terephthalic acid accounts for 70 mol% of the dicarboxylic acid unit, and isophthalic acid accounts for 30 mol% of the dicarboxylic acid unit, and is prepared by referring to the method described in the summary of the invention.

[0056] Polyarylate D: bisphenol A, terephthalic acid accounts for 30 mol% of the dicarboxylic acid unit, and isophthalic acid accounts for 70 mol% of the dicarboxylic acid unit, and is prepared by referring to the method described in the summary of the invention.

[0057] The glass fiber is chopped glass fiber purchased from China Jushi Co., Ltd., and then the experimental samples with corresponding average length are obtained by screening.

[0058] Glass fiber A: average length is 86.1 microns;

[0059] Glass fiber B: average length is 109.3 microns;

[0060] Glass fiber C: average length is 131.0 microns;

[0061] Glass fiber D: average length is 216.6 microns;

[0062] Glass fiber E: average length is 74.3 microns;

[0063] Glass fiber F: average length is 268.8 microns;

[0064] Talc powder was purchased from Guangxi Longsheng Huamei Talc Development Co., Ltd. and then screened to obtain raw materials with specific particle sizes.

[0065] Talc A: average particle size is 5.3 microns;

[0066] Talc B: average particle size is 11.5 microns;

[0067] Talc C: average particle size 20.2 microns;

[0068] Talc D: average particle size is 30.3 microns;

[0069] Talc E: average particle size is 2.5 microns;

[0070] Talc F: The average particle size is 43.8 microns.

[0071] Flake graphite: average particle size is 13.7 μm, purchased from Qingdao Tianyuan Graphite;

[0072] Mica powder: average particle size 12.4 μm, purchased from Liming Mineral Products Co., Ltd.;

[0073] Silane coupling agent: KBM-403, Shin-Etsu Sillcone silane coupling agent.

[0074] The preparation method of the liquid crystal polyester composition of the embodiment and the comparative example is as follows: the components are mixed uniformly, and then extruded into granules through a twin-screw extruder, the screw speed range is 400-600RPM, and the temperature range is 330-360°C to obtain a liquid crystal polyester composition.

[0075] Various test methods:

[0076] (1) Test method for the glass fiber retention length and average particle size of flaky fillers in liquid crystal polyester compositions: With reference to ISO3451-1, obtain the ash content in the liquid crystal polyester composition, place the ash in 100 mL of 95% industrial alcohol and disperse it with an ultrasonic machine for 2 min, then use a pipette to draw 2 mL from the bottom and place it on a clean glass slide, take a picture with an optical microscope at a magnification of 500 times, and calculate the average retention length and average particle size of the above fillers using statistical methods.

[0077] (2) Wear resistance: After extrusion granulation, a circular specimen with a diameter of 16 mm and a thickness of 8 mm was injection molded using an injection molding machine. Based on the DIN 53516 GB9867 wear resistance test method, a DIN wear resistance test machine was used, with a lateral displacement of the fixture of 4.2 ± 0.04 mm / roller turn, a roller diameter of 150 mm, a roller speed of 40 ± 1 RPM, and a 60# emery paper attached to the roller. A 250g weight was added to the upper end of the specimen fixing column. The specimen was subjected to one cycle of wear, and the mass before and after the test was measured to calculate the weight loss percentage.

[0078] (3) Heat and foaming resistance: Injection molded square specimens with a length of 60 mm and a thickness of 1 mm were placed in a hot air oven at 270°C for 30 min, and the number of bubbles on the specimens was observed and recorded.

[0079] Table 1: Components (parts by weight) and test results of the liquid crystal polyester compositions of Examples 1-8

[0080] Example 1 Example 2 Example 3 Example 4 Example 6 Example 7 Example 8 Liquid crystal polyester types A B C D A A A Liquid crystal polyester content 50 50 50 50 50 50 50 Glass fiber B content 10 10 10 10 4.5 39.2 10 Retention length, μm 101.3 100.6 100.9 102.4 101.2 100.1 100.5 Talc B content 10 10 10 10 7.5 0.8 10 Average particle size, micrometer 10.8 10.6 10.1 10.7 10.5 10.9 10.4 Coupling agent content 0.5 0.5 0.5 0.5 0.1 3 0.5 LLDPE content 0.4 0.4 0.4 0.4 0.2 0.6 0.2 Polyarylate A content 2.5 2.5 2.5 2.5 1 4 1 Wear resistance, % 8 7 7 8 15 14 9 Number of foams, 0 0 0 0 0 6 0

[0081] It can be seen from Examples 1 / 8-10 that the preferred LLDPE / polyarylate content range has better wear resistance, heat resistance and foaming resistance.

[0082] Table 2: Components (parts by weight) and test results of the liquid crystal polyester compositions of Examples 9-15

[0083] Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 Liquid crystal polyester A content 50 50 50 50 50 50 50 Glass fiber samples B B A C D E F Glass fiber content 10 10 10 10 10 10 10 Retention length, μm 100.4 101.1 81.2 119.1 197.4 62.0 241.6 Talc powder sample B B A C D E F Talc content 10 10 10 10 10 10 10 Average particle size, micrometer 10.7 10.5 5.1 19.4 28.9 2.3 42.3 Coupling agent content 0.5 0.5 0.5 0.5 0.5 0.5 0.5 LLDPE content 0.5 0.6 0.4 0.4 0.4 0.4 0.4 Polyarylate A content 3 4 2.5 2.5 2.5 2.5 2.5 Wear resistance, % 8 10 8 9 10 7 11 Number of foams, 0 2 2 0 2 5 4

[0084] It can be seen from Examples 1 / 10-15 that the preferred fiber retention length and average particle size range of the flaky filler have better wear resistance and less foaming amount.

[0085] Table 3: Components (parts by weight) and test results of the liquid crystal polyester compositions of Examples 16-20

[0086] Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Liquid crystal polyester A content 50 50 50 50 50 Glass fiber B content 10 10 10 10 10 Retention length, μm 101.0 100.6 100.3 100.1 100.7 Flake graphite content 10 10 10 10 Mica content 10 Average particle size, micrometer 10.2 11.0 10.6 10.1 10.6 Coupling agent content 0.5 0.5 0.5 0.5 0.5 LLDPE content 0.4 0.4 0.4 0.4 0.4 Polyarylate A content 2.5 2.5 Polyarylate B content 2.5 Polyarylate C content 2.5 Polyarylate D content 2.5 Wear resistance, % 7 8 9 11 10 Number of foams, 0 0 0 0 0

[0087] It can be seen from Examples 13 / 18-20 that the polyarylate with the preferred repeating unit has better wear resistance.

[0088] Table 4: Components (parts by weight) and test results of the liquid crystal polyester compositions of Examples 20-24

[0089] Embodiment 21 Embodiment 22 Embodiment 23 Embodiment 24 Liquid crystal polyester A content 50 50 50 50 Glass fiber B content 7.5 13.3 17.5 19.6 Retention length, μm 100.2 100.8 101.9 102.3 Talc B content 12.5 6.7 2.5 0.4 Average particle size, micrometer 10.8 10.5 10.2 10.1 Coupling agent content 0.5 0.5 0.5 0.5 LLDPE content 0.4 0.4 0.4 0.4 Polyarylate A content 2.5 2.5 2.5 2.5 Wear resistance, % 6 4 4 12 Number of foams, 0 0 0 0

[0090] It can be seen from Examples 1 / 21-24 that when the preferred weight ratio of fibrous filler to flaky filler is (2-7):1, the wear resistance is better.

[0091] Table 5: Components (parts by weight) and test results of comparative liquid crystal polyester compositions

[0092] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Liquid crystal polyester types E F G H A A A A Liquid crystal polyester content 50 50 50 50 50 50 50 50 Glass fiber B content 10 10 10 10 10 10 10 10 Retention length, μm 100.9 101.2 99.8 100.5 100.2 100.4 101.5 99.4 Talc B content 10 10 10 10 10 10 10 10 Average particle size, micrometer 10.5 10.2 10.6 10.8 10.7 11.1 10.2 10.5 Coupling agent content 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 LLDPE content 0.4 0.4 0.4 0.4 0.1 0.8 0.5 0.5 Low density polyethylene content Polyarylate A content 2.5 2.5 2.5 2.5 2.5 2.5 0.5 5 Wear resistance, % 10 7 9 9 14 9 13 11 Number of foams, 7 4 3 6 0 3 2 17

[0093] It can be seen from Comparative Examples 1-4 that other types of liquid crystal polyesters cannot achieve the purpose of the present invention.

[0094] It can be seen from Comparative Examples 5-8 that if the content of LLDPE and polyarylate is not within the scope of the present invention, the wear resistance, heat resistance and foaming resistance are poor.

[0095] Table 5 continued:

[0096] Comparative Example 9 Comparative Example 10 Comparative Example 11 Liquid crystal polyester types A A A Liquid crystal polyester content 50 50 50 Glass fiber B content 10 10 10 Retention length, μm 101.4 101.3 100.7 Talc B content 10 10 10 Average particle size, micrometer 10.3 10.1 10.4 Coupling agent content 0.5 0.5 0.5 LLDPE content 3 Low density polyethylene content 0.5 Polyarylate A content 2.5 3 Wear resistance, % 8 14 13 Number of foams, 5 4 9 .

Claims

1. A liquid crystal polyester composition, characterized in that: By weight, it includes the following components: Liquid crystal polyester 50-100 parts; 12-40 parts of filler; Coupling agent 0.1-3 parts; LLDPE 0.2-0.6 parts; 1-4 parts of polyarylate; Wherein, the filler is selected from fibrous filler and flaky filler, and the weight ratio of fibrous filler to flaky filler is (0.6-50):1; The liquid crystal polyester is composed of at least two of terephthalic acid, biphenol, 6-hydroxy-2-naphthoic acid, and p-hydroxybenzoic acid and acetaminophen as repeating units; The flaky filler is selected from at least one of talcum powder, flake graphite and mica, and the fibrous filler is selected from at least one of glass fiber and carbon fiber.

2. The liquid crystal polyester composition according to claim 1, characterized in that: The weight ratio of the fibrous filler to the flaky filler is (2-7):

1.

3. The liquid crystal polyester composition according to claim 1, characterized in that: The weight portion of LLDPE is 0.3-0.5 parts, and the weight portion of polyarylate is 2-3 parts.

4. The liquid crystal polyester composition according to claim 1, characterized in that: The polyarylate is composed of diphenol units and dicarboxylic acid units. The diphenol units are derived from bisphenol A. In terms of molar percentage of dicarboxylic acid units, terephthalic acid accounts for 40-60 mol% of the dicarboxylic acid units, and isophthalic acid accounts for 40-60 mol% of the dicarboxylic acid units.

5. The liquid crystal polyester composition according to claim 1, characterized in that: The retention length of the fibrous fillers ranges from 80-200 microns.

6. The liquid crystal polyester composition according to claim 5, characterized in that: The retention length of the fibrous fillers ranges from 95-120 microns.

7. The liquid crystal polyester composition according to claim 1, characterized in that: The average particle size of the plate-like filler is in the range of 5-30 microns.

8. The liquid crystal polyester composition according to claim 7, characterized in that: The average particle size of the plate-like filler is in the range of 10-20 microns.

9. The liquid crystal polyester composition according to claim 1, characterized in that: The coupling agent is selected from at least one of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent.

10. The liquid crystal polyester composition according to claim 9, characterized in that: The coupling agent is selected from silane coupling agents.

11. The liquid crystal polyester composition according to claim 1, characterized in that: By weight, 0-1 part of antioxidant is also included.

12. The method for preparing the liquid crystal polyester composition according to any one of claims 1 to 11, characterized in that: The method comprises the following steps: mixing the components uniformly, extruding and granulating, and obtaining a liquid crystal polyester composition.

13. Use of the liquid crystal polyester composition according to any one of claims 1 to 11, characterized in that: Used to prepare thin-walled housings for electrical appliances.